2002
DOI: 10.1021/jp021966v
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Reactivity of Al2O3-Supported Cobalt−Palladium Particles:  A CO-TPD, STM, and XPS Study

Abstract: Bimetallic Co−Pd Fischer−Tropsch catalysts have shown increased activity toward CO-hydrogenation and methane conversion. A model for these Fischer−Tropsch catalysts has been constructed and studied under ultrahigh vacuum conditions. The morphology, growth modes, exposed binding sites, and electronic properties of Co−Pd bimetallic particles supported on a thin alumina film have been studied using scanning tunneling microscopy (STM), temperature-programmed desorption (TPD) of CO, and X-ray photoelectron spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 47 publications
7
66
0
Order By: Relevance
“…Carlsson et al [48] showed that in Co-Pd alumina supported systems, the binding energy of carbon monoxide to both Pd and Co sites was lowered in the presence of the other metal. Formation of bimetallic particles resulted in net polarization of charge or redistribution of d-band states.…”
Section: Formation Of Bimetallic Particlesmentioning
confidence: 99%
“…Carlsson et al [48] showed that in Co-Pd alumina supported systems, the binding energy of carbon monoxide to both Pd and Co sites was lowered in the presence of the other metal. Formation of bimetallic particles resulted in net polarization of charge or redistribution of d-band states.…”
Section: Formation Of Bimetallic Particlesmentioning
confidence: 99%
“…5,6 The formation of alloy particles on thin oxide films has recently been characterized using scanning tunneling microscopy ͑STM͒ and electron and infrared spectroscopy. [7][8][9] In contrast to bulk alloys, the intermixing in small particles depends on several additional parameters, such as diffusivity, nucleation and growth of the compounds on the oxide support, their surface free energy and miscibility, and the thermodynamic alloying conditions. As a result, it often remains unclear if the compounds completely mix to alloy clusters, form shell-core structures with different composition of inner and outer layer or separate into monoelemental clusters on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong propensity to form lower coordinated metal atoms on the nanoparticle at low temperature, as may be identified by IRAS studies . Co particles loose those low coordinated sites and sinter upon temperature increase as revealed by STM (Carlsson et al 2003c), ferromagnetic resonance (FMR (Hill et al 2005, Risse et al 2004), and IRAS measurements (Carlsson et al 2003c). The latter technique delivers detailed insight not only into sintering but also into the rearrangement at the surfaces of the particles, including the metal oxide interface.…”
Section: Martin Schmal and Hans-joachim Freundmentioning
confidence: 99%